2008
DOI: 10.1161/circresaha.108.174615
|View full text |Cite
|
Sign up to set email alerts
|

Role of the ATP-Binding Cassette Transporter Abcg2 in the Phenotype and Function of Cardiac Side Population Cells

Abstract: Abstract-Recently, the side population (SP) phenotype has been introduced as a reliable marker to identify subpopulations of cells with stem/progenitor cell properties in various tissues. We and others have identified SP cells from postmitotic tissues, including adult myocardium, in which they have been suggested to contribute to cellular regeneration following injury. SP cells are identified and characterized by a unique efflux of Hoechst 33342 dye. Key Words: Abcg2 Ⅲ Mdr1 Ⅲ progenitor cells Ⅲ proliferation Ⅲ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 24 publications
(34 reference statements)
2
103
1
3
Order By: Relevance
“…This unique property is mediated through the action of the ATP-binding cassette transporter proteins ABCG2 (Zhou et al, 2001) and Abcb1/Mdr1 (Pfister et al, 2008) expressed on the cell surface. SP cells with stem cell-like properties in adult hearts were first reported by Hierlihy et al (2002).…”
Section: Resident Cscs Sca1 1 /Cd31 2 Cardiac Sp Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This unique property is mediated through the action of the ATP-binding cassette transporter proteins ABCG2 (Zhou et al, 2001) and Abcb1/Mdr1 (Pfister et al, 2008) expressed on the cell surface. SP cells with stem cell-like properties in adult hearts were first reported by Hierlihy et al (2002).…”
Section: Resident Cscs Sca1 1 /Cd31 2 Cardiac Sp Cellsmentioning
confidence: 99%
“…Recent studies indicate that ABCG2 is important for cytoprotection and for regulating the function and homeostasis of CSP cells. Using a loss-and gain-of-function strategy, Pfister et al (2008) demonstrated that adult CSP cells isolated from ABCG2 knockout mice exhibited a blunted proliferation capacity, leading to increased cell death. In contrast, overexpression of ABCG2 significantly enhanced CSP cell proliferation but limited their capacity for cardiomyogenic differentiation.…”
Section: Resident Cscs Sca1 1 /Cd31 2 Cardiac Sp Cellsmentioning
confidence: 99%
“…Two ABC transporter superfamily members, Abcg2 and Multidrug resistance (Mdr)1, drive Hoechst dye efflux, and by their differentially enriched expression in stem cells constitute the probable basis of the SP phenotype. Genetic studies indicate that Abcg2 regulates the proliferative capacity and survival of the adult cardiac SP (35). Enriched Abcg2 expression in embryonic and fetal hearts suggests that this transporter also plays a prominent role during cardiac development (18).…”
Section: Increased Abcg2 and Altered Cardiac Stem/differentiation Genementioning
confidence: 99%
“…The efflux of Hoechst dye is attributed to members of the ABC family of membrane pumps, with ABCG2 and ABCB1 identified as likely mediators of Hoechst efflux (Pfister et al, 2008;Dean et al, 2009). ABCG2 protein plays an important role DOI:http://dx.doi.org/10.7314/APJCP.2013.14.12 in the drug resistance of normal stem cells and tumor stem cells, and is a molecular determinant of the SP phenotype (Zhou et al, 2001;Dean et al, 2009).…”
Section: Discussionmentioning
confidence: 99%